Melamine disrupts spatial reversal learning and learning strategy via inhibiting hippocampal BDNF-mediated neural activity. - Wei Sun; Yuanhua Wu; Dongxin Tang; Xiaoliang Li; Lei An (PLoS ONE, 2021)
Although several studies showed adverse neurotoxic effects of melamine on hippocampus (HPC)-dependent learning and reversal learning, the evidence for this mechanism is still unknown. We recently demonstrated that intra-hippocampal melamine injection affected the induction of long-term depression, which is associated with novelty acquisition and memory consolidation. Here, we infused melamine into the HPC of rats, and employed behavioral tests, immunoblotting, immunocytochemistry and electrophysiological methods to sought evidence for its effects on cognitive flexibility. Rats with intra-hippocampal infusion of melamine displayed dose-dependent increase in trials to the criterion in reversal learning, with no locomotion or motivation defect. Compared with controls, melamine-treated rats avoided HPC-dependent place strategy. Meanwhile, the learning-induced BDNF level in the HPC neurons was significantly reduced. Importantly, bilateral intra-hippocampal BDNF infusion could effectively mitigate the suppressive effects of melamine on neural correlate with reversal performance, and rescue the strategy bias and reversal learning deficits. Our findings provide first evidence for the effect of melamine on cognitive flexibility and suggest that the reversal learning deficit is due to the inability to use place strategy. Furthermore, the suppressive effects of melamine on BDNF-mediated neural activity could be the mechanism, thus advancing the understanding of compulsive behavior in melamine-induced and other neuropsychiatric disorders.